Extracellular pyridine nucleotides as immune elicitors in arabidopsis. (2nd November 2017) - Mou, Zhonglin
ABSTRACT: The pyridine nucleotides nicotinamide adenine dinucleotide (NAD) and NAD phosphate (NADP) are coenzymes that function in both metabolic reactions and intracellular signaling. Emerging evidence from animal research indicates that NAD(P) also acts in the extracellular space (ECS). We have shown in the model plant Arabidopsis that (1) exogenous NAD(P) induces immune responses, (2) pathogen infection causes leakage of intracellular NAD(P) into the extracellular fluid at concentrations sufficient to induce immune responses, and (3) removal of extracellular NAD(P) [eNAD(P)] by expressing the human NAD(P)-metabolizing ectoenzyme CD38 partially compromises systemic acquired resistance. Based on these results, we hypothesize that eNAD(P) is a novel damage-associated molecular pattern (DAMP) in plants; during plant-microbe interaction, intracellular NAD(P) is released from dead or dying cells into the ECS where it interacts with the adjacent healthy cells' surface receptors/targets, which in turn activate downstream specific immune signaling pathways. Our recent identification of LecRK-I.8, a lectin receptor kinase, as the first cell surface NAD + -binding receptor has provided compelling evidence for this hypothesis. Further identification of cell surface eNAD(P) receptors/targets and their downstream signaling components in Arabidopsis as well as determination of the generality of eNAD(P) signaling in crops will help establish eNAD(P) as a conserved DAMP in plants.